Studying the Downstream Effects of Fact-Checking on Social Media: Experiments on Correction Formats, Belief Accuracy, and Media Trust - Ingrid Bachmann; Sebastián Valenzuela (Social Media + Society, 2023)
Repeated exposure to misinformation not only reduces the accuracy of people’s beliefs, but it also decreases confidence in institutions such as the news media. Can fact-checking—journalism’s main weapon against misinformation—worsen or ameliorate distrust in journalists and the media? To answer this question, we conducted two pre-registered experiments in Chile (total N  = 1,472) manipulating message and receiver factors known to regulate the persuasiveness of fact-checks: transparency elements, arousing images, and political alignment. The results of both studies show that, across message formats, fact-checks are similarly effective at reducing people’s misperceptions. However, these positive effects on belief accuracy come at a cost: Compared to control groups, users exposed to political fact-checks trust news less and perceive the media as more biased, especially after reading corrections debunking pro-attitudinal misinformation. We close with a discussion of the theoretical and practical implications of these findings.